The Aesthetic Value of Costume Design in Semarang Night Carnival - Budiharti, Budiharti; Syakir, Syakir; Naam, Muhamad fakhrihun (Universitas Negeri Semarang, 2019)
Semarang Night Carnival (SNC) is a yearly costume design show from the creativity of the youth of Semarang and its surrounding areas which brings unique and interesting themes and has an aesthetic value. There are four themes that has enliven the 7th SNC in 2018 in Semarang City, they are, defile, Masquerede Gold (Batik Semarangan), Masquerede silver (Art Deco) taking the theme of Lawang Sewu, Masquerede Red (Pelangi village) and Masquirade Blue (Coast). This study aims to reveal the aesthetic values contained in the Semarang Night Carnival (SNC) costume design in Semarangan culture used in the Semarang City Anniversary activities in 2018. The benefits of research can give contributions to all parties regarding the existence of SNC both theoretically and practically. The research method used descriptive qualitative methods. Data collection techniques were obtained by observation, interview and documentation study. Data analysis used data collection, data reduction, data presentation, and conclusion drawing. The results showed that the costume design worn by the participants of the Semarang Night Carnival had an aesthetic value according to the property of something being valued, according to himself or according to other sources of value in accordance with the theme carried. The Semarang Night Carnival costume design worn by the participants included asem arang costume, butterfly costume, lawang sewu costume and beach costume.